ANALYSIS OF THE CONSTITUTIONAL COURT’S LEGAL CONSIDERATIONS IN DECISION NUMBER 63/PUU-XIV/2016 REGARDING THE JUDICIAL REVIEW OF THE TAX AMNESTY LAW AGAINST THE 1945 CONSTITUTION (Jurnal Masyrakat Indonesia Harapan, 2025)
This legal research aims to analyze and elaborate on the legal considerations or ratio decidendi applied by the Constitutional Court of the Republic of Indonesia in rendering Decision Number 63/PUU-XIV/2016 concerning the judicial review of Law Number 11 of 2016 on Tax Amnesty against the 1945 Constitution of the Republic of Indonesia. Since its enactment, the Tax Amnesty Law has sparked significant public controversy, particularly concerning issues of fairness for compliant taxpayers and its potential impact on efforts to eradicate corruption and money laundering. These issues became the central arguments raised by the Petitioners in the judicial review submitted to the Constitutional Court. Fundamentally, this controversy touches upon key constitutional principles, particularly Article 27 paragraph (1) regarding equality before the law, Article 28D paragraph (1) concerning recognition, guarantees, protection, and fair legal certainty, and Article 23A relating to taxes and other compulsory levies regulated by law.The research employs normative legal research with a case approach, focusing on an in-depth analysis of the Constitutional Court’s decision documents, including the petitum, contra-petitum, opinions of the parties, and most importantly, the Court’s overall legal reasoning. The results of the analysis show that the Constitutional Court, while ultimately rejecting the Petitioners’ request in its entirety, exercised a highly cautious and prudent constitutional interpretation to balance the urgent need of the state to recover the economy through massive tax revenues with adherence to the principles of the rule of law and social justice enshrined in the 1945 Constitution.The Court affirmed that tax amnesty is a discretionary and temporary policy justified under conditions of economic emergency and cannot be considered a permanent policy that undermines the national taxation system or empowers offenders. Specifically, the Court provided a binding interpretation of the term “exception” within the Tax Amnesty Law, explicitly stating that the amnesty scheme does not erase the criminal status of offenses such as corruption, narcotics, or terrorism, but only applies to tax-related crimes. This interpretation is recognized as a form of constitutional limitation — an absolute mechanism to safeguard the integrity of the Constitution while mitigating public concerns over impunity for serious crimes.